(untitled) (Itinera, 2020)
«The ox becomes furious if a red cloth is shown to him, but the philosopher, who speaks of colour only in a general way, begins to rave». This is still true now: the philosophical discussion on colour is very lively. There is a debate within Anglo-American philosophy that has been going on for the past fifty years, and is still going on today, as is demonstrated by the imminent publication of the Routledge Handbook of Philosophy of Colour, which we are happy to announce in this issue. Colour is something very familiar but, nevertheless, it is also a subject on which philosophers never cease to raise questions. Why?